Effects of match forms and outcomes on phase-based elite male table tennis match performance - Yu, J.; Cui, Y.; Xiao, D. (Kinesiology, 2022)
The aim of the study was to explore the service round technical-tactical performance indicators of three phases discriminating the match result and the two match forms. The statistics of 72 professional men`s singles matches of the 2018 international competitions were collected. A chi-square test was used to assess the relationship between match form, match outcome and service round result. Afterwards, a two-way ANOVA was performed to evaluate the effect of match form (SHM: match between players of the same handedness and OHM: match between players of the opposite handedness) and match result on three evaluation indices of thirteen technical-tactical indicators. The results displayed that: (1) there was a weak relationship between the service round outcome and match form for both the winning and losing players (p<0.001, ES=0.12); (2) the winners outperformed the defeated players by a higher technical effectiveness in all three phases with small to moderate effects (p<0.05, ES:0.50-1.00) at both match forms; (3) the usage rate of performance indicators of the first four strokes phase and six strokes above phase distinguished the SHM matches from the OHM matches by small to large effects (p<0.05, ES:0.50-1.26). This study offers insights for practitioners to comprehend the technical-tactical aspects that are deciding for performance when competing against different types of opponents and to make effective training plans and match strategies.